The Effectiveness of the Implementation of the Regulation of the Minister of ATR/BPN No. 18 of 2021 in the Process of Increasing the Use Rights to the Building Rights (Study at the Cirebon City Land Office) - Gultom, Ruth Elita (Universitas Negeri Semarang, 2026)
Land administration reform through the Ministerial Regulation of ATR/BPN Number 18 of 2021 directed to build a mechanism for determining and changing land rights that is integrated, efficient, and guarantees legal certainty. One form of strategic change of rights is the increase of the Right of Use to the Right to Use (HGB), which has significant implications for the optimization of the economic value of land assets. This study aims to examine the effectiveness of the implementation of the Minister of ATR/BPN Regulation No. 18 of 2021 in the process of increasing the Right of Use to become HGB at the Cirebon City Land Office. The method used is empirical juridical with descriptive-analytical specifications through interviews, document studies, and the study of laws and regulations and scientific literature. The results of the study show that normatively and procedurally, regulations have been implemented in accordance with the applicable legal framework, reflecting the effectiveness of the substance and implementation structure aspects. Simultaneous mechanisms, physical and juridical data research, and service operational standards run consistently without administrative irregularities. Although one of the applications for the increase of procedural rights did not reach the finalization stage, this condition reflects more the dynamics of fulfilling continued administrative obligations than the weaknesses of the regulations. Thus, the Minister of ATR/BPN Regulation No. 18 of 2021 can be considered effective in its normative and administrative scope, while the effectiveness of its practice is still influenced by external factors that are outside the boundaries of land regulation regulation.